Causal Interactions between Frontalθ – Parieto-Occipitalα2 Predict Performance on a Mental Arithmetic Task - Dimitriadis, Stavros I.; Sun, Yu; Thakor, Nitish V.; Bezerianos, Anastasios (Frontiers in Human Neuroscience, 2016)
Many neuroimaging studies have demonstrated the different functional contribution of spatial distinct anatomical brain areas to working memory (WM) subsystems in various cognitive tasks that demand both local information processing and a coordinated mechanism between them. In WM cognitive tasks using electroencephalography (EEG), brain rhythms, such as θ and α, have been linked to a specific functional role located over a brain area but their functional coupling has not been yet studied extensively. In the present study, analyzing an arithmetic task designed with five cognitive workload levels (CWLs), we demonstrated the functional/effective coupling between the two subsystems of the WM, the central executive located over frontal (F) brain areas that oscillates on the dominant θ rhythm (Frontalθ/Fθ) and the storage buffer located over parieto-occipital (PO) brain areas that operates on the α2 dominant brain rhythm (Parieto-Occipitalα2 / POα2). Our analysis focused on demonstrating important differences between and within WM subsystems in relation to behavioral performance. Attempting to uncover the distinct role of amplitude, phase within and between frequencies and also the hierarchical role of functionally specialized brain areas related to the task, we employed a repertoire of brain connectivity estimators. Specifically, for each CWL, we conducted a) a conventional signal power analysis within both frequency bands at Fθ and POα2 ,b) the intra and inter-frequency phase interactions between Fθ and POα2 and c) their causal phase and amplitude relationship. We found no significant statistical difference of signal power and of phase interactions between correct and wrong answers. Interestingly, the study of causal interactions between Fθ and POα2 revealed frontal brain region(s) as the leader, while the strength was able to differentiate correct from wrong responses, in every CWL with absolute accuracy. Additionally, zero time-lag between bilateral Fθ and right POa2 could serve as an indicator of the failure in mental calculation. Overall, our study highlights the significant role of coordinated activity between Fθ and POα2 via their causal interactions and the timing for arithmetic performance.